2016
DOI: 10.4269/ajtmh.15-0553
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Structured Predeparture Orientation at the David Geffen School of Medicine's Global Health Education Programs

Abstract: Abstract. Given the lack of a standardized approach to medical student global health predeparture preparation, we evaluated an in-person, interactive predeparture orientation (PDO) at the University of California Los Angeles (UCLA) to understand program strengths, weaknesses, and areas for improvement. We administered anonymous surveys to assess the structure and content of the PDO and also surveyed a subset of students after travel on the utility of the PDO. We used Fisher's exact test to evaluate the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…For the teacher, in general, studies show that this preparation is even more challenging, as students [15,16] need to exchange information, experiences, and flexibility beyond traditional teaching standards. For this, teachers and students need to learn how to optimize existing resources and work as a team with other professions, reinforcing the importance of cross-disciplinary work [17][18][19].…”
Section: Class 1 -Students' Preparation For Gh Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the teacher, in general, studies show that this preparation is even more challenging, as students [15,16] need to exchange information, experiences, and flexibility beyond traditional teaching standards. For this, teachers and students need to learn how to optimize existing resources and work as a team with other professions, reinforcing the importance of cross-disciplinary work [17][18][19].…”
Section: Class 1 -Students' Preparation For Gh Experiencesmentioning
confidence: 99%
“…As a complementary aspect of student preparation, our findings point to teaching emotional, cultural, and collaborative skills to teach and develop the values and principles of team-building to plan and execute the project goals. This experience allows the student to apply leadership tools that support collaborative practice, through values and principles of respect for cultural diversity [17].…”
Section: Class 2 -Emotional Cultural and Collaborative Aspects In Tmentioning
confidence: 99%
“…Practitioners with experience in GCH contribute to the growing demand for global health education by offering mentorship and career guidance through academic institutions 97,98 and national and international associations, such as the AAP International Community Access to Child Health program and the Consortium of Universities for Global Health Program Advisory Service. These and other professional associations with GCH interest sections provide informal networking opportunities and can be a repository of lessons learned and a source of clinical and professional guidance.…”
Section: Mentorshipmentioning
confidence: 99%
“…A Canadian study of medical school faculty also noted gaps in pre-departure planning and concluded that reviews of health and safety should be mandatory for all international electives 34 . A few studies have documented student satisfaction with health and safety training, but they lack details about what safety training their programs covered 35 , 36 …”
Section: Risks and Challengesmentioning
confidence: 99%